7DCT Transmission efficiency optimization: Design and simulation of oil traps that reduce the churning los - Forsström, Birk; Minar, Matus (My University, 2020)
The automotive industry is undergoing a big change when switching from building combustion engine cars to electric powered cars. With the big limitation of range that comes with using battery to store energy there is an even greater need in finding ways to improve the efficiency. Together with CEVT (China Europe Vehicle Technology), this master’s thesis purpose is to make an improvement of the gearbox that lower the torque that is required to rotate it. To verify the results a prototype is built with materials available in the company’s workshop and investigated if it can withstand a test in a testing rig. With the use of CFD-analysis (Computational Fluid Dynamics) the lubricant of the gears is investigated through a simulation of a benchmark. The aim was to find areas where reduction of churning losses can be made with the use of a new part that is created in CAD (Computer Aided Design). Inspiration for these improvements is found in previous studies made by employees at CEVT and at rival companies. The process of creating a new part is iterative and performed with rough simulations before a comprehensive simulation is made that can be compared with the benchmark. Through the benchmark simulation it was concluded that the differential gear stands for most of the churning losses along with the output shaft above it. A new part was created that protects the top shaft from being hit by incoming oil transported by the differential, it also collects the oil in two containers for further redistribution. These changes resulted in a decrease in drag torque generated by the oil of 16.3% at 50km/h and a trend of larger reduction at higher speeds. For a prototype build, experimental tests were conducted on the ABS-plastic available at the company. It was concluded that the plastic would withstand the heat and oil inside of the gearbox and afterwards a prototype was built for future testing. In the end of the study it was concluded that oil can be collected in the upper regions of the gearbox by taking care of the splash from gears. This along with protecting gears from splash that hit them in the opposite direction of speed can reduce the churning losses by around 16%. With this knowledge a future work would be to investigate how to distribute this oil from these regions to where it is needed. By doing so, future development of gearboxes can be made around how oil is being transported by gears to benefit from these possibilities.